Redacción impura Periodismo de opinión - Pancani, Dino (Ariadna Ediciones, 2021)
The tour that Dino Pancani invites us to includes the writings he disseminated in the digital newspaper El Mostrador and the most recent in the column section of the Cooperativa radio station edited by the journalist Manola Robles, who left us a few months ago. The selection of the articles is not chronological, nor is it random, but rather has a logic that readers understand as we turn the pages, with the memory aid of the titles of the different chapters or sections. It is a division by major themes to which the author devoted special time and attention at his time, because of what he was observing with his critical and inquisitive gaze or because of the reminiscences they brought to him. Some lived them as a protagonist or witness. Others studied them or on them has stopped to reflect until today. But there is something very special in these writings. An interesting mix of styles, almost a hybrid between the expression of his committed and challenging thinking and the story rich in descriptions. Between the column and the chronicle. Between a journalism of clear, clear and strong opinion that with arguments tries to demonstrate to the reader the validity of its judgment on a certain topic and an attractive chronicle abundant in nouns and especially in adjectives that give color and life to what it exposes.